2021
DOI: 10.3390/ijms222111939
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Transcription Factor Nrf2 in Cardiac Ischemia–Reperfusion Injury

Abstract: Nuclear factor erythroid-2 related factor 2 (Nrf2) is a transcription factor that controls cellular defense responses against toxic and oxidative stress by modulating the expression of genes involved in antioxidant response and drug detoxification. In addition to maintaining redox homeostasis, Nrf2 is also involved in various cellular processes including metabolism and inflammation. Nrf2 activity is tightly regulated at the transcriptional, post-transcriptional and post-translational levels, which allows cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 233 publications
(290 reference statements)
0
26
0
Order By: Relevance
“…Besides the liver, these Nrf2‐mediated antioxidant mechanisms have also been described during IR in the brain [58–60], heart [61–63], and kidney [64–66].…”
Section: Nrf2 As a Transcription Factor: Cellular And Molecular Funct...mentioning
confidence: 99%
“…Besides the liver, these Nrf2‐mediated antioxidant mechanisms have also been described during IR in the brain [58–60], heart [61–63], and kidney [64–66].…”
Section: Nrf2 As a Transcription Factor: Cellular And Molecular Funct...mentioning
confidence: 99%
“…Keap1 is a polypeptide composed of 624 amino acid residues and 5 domains: NTR (N-terminus), IVR, BTB/POZ DGR, and CTR (C-terminus). Scientific research established in cell lines and animal models that Nrf2/Keap1 pathway activation exerts protective effects in ischemia–reperfusion injury in vessels [ 68 ].…”
Section: Nrf2mentioning
confidence: 99%
“…Nrf2 is a transcription factor that controls cellular defense responses [ 199 ], particularly in the regulation of the expression of antioxidant and detoxification genes [ 199 , 200 , 201 ]. Nrf2 is known to protect cardiomyocytes against oxidative stress by increasing endogenous antioxidants [ 202 , 203 ].…”
Section: Modification Of I/r-induced Defects In Signal Transductionmentioning
confidence: 99%
“…In fact, several studies have shown that the activation of Nrf2 and the subsequent upregulation of antioxidant enzyme gene expression is an important mechanism of cardioprotection due to ischemic/hypoxic preconditioning, and that low concentrations of ROS may be an essential signal for the protective process [ 212 , 213 , 214 , 215 ]. Furthermore, Nrf2 has also been reported to modulate intracellular Ca 2+ levels [ 216 ], and thus cardioprotection against I/R injury due to the activation of Nrf2 has recently been explored for clinical applicability [ 199 ]. In addition, the role of Nrf2 signal transduction in the protective actions of IP has also been examined [ 212 , 217 ].…”
Section: Modification Of I/r-induced Defects In Signal Transductionmentioning
confidence: 99%